How does climate change affect the evidence we need for agricultural development?. (22nd July 2022) - Lipper, Leslie; Puri, Jyotsna; Cavatassi, Romina; McCarthy, Nancy
Abstract: Evidence‐based knowledge has been a critical element for designing effective investments into agricultural transformation, particularly in recent years. Now, however, climate change alters the nature of the knowledge and supporting evidence needed. That leads to the main question we address in this article – how climate change affects the evidence needed to support agricultural transformation. We look at the issue through the lens of the multilateral development banks, and in particular the International Fund for Agricultural Development (IFAD). We suggest three major approaches to addressing the shortfalls in the current evidence base: (1) better synthesis of information that is currently available to increase its utility in designing new investments, (2) improving the information we gather to better provide the evidence base on why and how transformative changes occur, and (3) much greater attention to mechanisms to help bridge the research/policy divide.